2019
DOI: 10.3389/fnagi.2019.00207
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Silencing of Fatty Acid Desaturases Modulates α-Synuclein Toxicity and Neuronal Loss in Parkinson-Like Models of C. elegans

Abstract: The molecular basis of Parkinson’s disease (PD) is currently unknown. There is increasing evidence that fat metabolism is at the crossroad of key molecular pathways associated with the pathophysiology of PD. Fatty acid desaturases catalyze synthesis of saturated fatty acids from monounsaturated fatty acids thereby mediating several cellular mechanisms that are associated with diseases including cancer and metabolic disorders. The role of desaturases in modulating age-related neurodegenerative manifestations su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 53 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Unbiased lipidomic analyses of cells or mice expressing toxic α-synuclein showed that accumulation of lipid droplets, unsaturated fatty acids, and triglycerides is a conserved pathological feature of α-synuclein models from yeast through mice [7]. The ability of SCD inhibition to mitigate α-synuclein toxicity phenotypes in multiple independent reports and disease models speaks to the robustness of the protective benefit of reducing monounsaturated fatty acids [5,[7][8][9][10]. Recent electron microscopic evaluation of Lewy body pathology in Parkinson's disease has identified early-stage Lewy bodies to consist of membranous organelles with aggregated α-synuclein [11].…”
Section: Introductionmentioning
confidence: 99%
“…Unbiased lipidomic analyses of cells or mice expressing toxic α-synuclein showed that accumulation of lipid droplets, unsaturated fatty acids, and triglycerides is a conserved pathological feature of α-synuclein models from yeast through mice [7]. The ability of SCD inhibition to mitigate α-synuclein toxicity phenotypes in multiple independent reports and disease models speaks to the robustness of the protective benefit of reducing monounsaturated fatty acids [5,[7][8][9][10]. Recent electron microscopic evaluation of Lewy body pathology in Parkinson's disease has identified early-stage Lewy bodies to consist of membranous organelles with aggregated α-synuclein [11].…”
Section: Introductionmentioning
confidence: 99%
“…HLEA-P3 treatments at doses of 5 and 25 μg/mL significantly reduced lipid deposition to 54.13% and 54.87%, respectively ( p < 0.05) ( Figure 5 A,B). Silencing of stearoyl-CoA desaturase-1 (SCD-1), a key enzyme in fatty acid metabolism, was shown to reduce lipid content and α-synuclein-induced neurotoxicity [ 27 ]. This study examined whether HLEA-P3 downregulated fat-5 , fat-6 and fat-7 (SCD-1 homolog) in NL5901 worms ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…This prompted us to speculate about a bi-directional scenario in which αS leads to elevated OA levels, which—after incorporation into membrane lipids—increase αS membrane association and toxicity ( 43 ). Indeed, we and others have demonstrated that loss/inhibition of the OA-generating enzyme stearoyl-CoA desaturase (SCD) rescues αS-related toxicity in yeast ( 41 , 44 ), Caenorhaditis elegans ( 41 , 45 ), primary rodent neurons ( 41 ) and neuroblastoma cells ( 42 ). The increased cellular viability was found to be accompanied by the following changes in αS homeostasis: (1) αS serine-129 phosphorylation of αS E46K and excess wt αS was reduced upon SCD inhibition ( 41 , 42 ); (2) αS E46K solubility, as assessed by cytosol:membrane ratio in sequential extraction experiments, was increased ( 41 , 42 ) and (3) inclusion formation of αS 3K (amplified E46K) was reduced ( 41 , 42 ).…”
Section: Resultsmentioning
confidence: 99%